Experimenting text input methods in mobile application / Anuar Mohd Yusof - Mohd Yusof, Anuar (2005)
Via the use of mobile phones, the Short Message Service (SMS) is the one of the most important mobile applications for communication between two or more people. Moreover, the effectiveness on typing messages needed to be improved in the area of the typing performance. When the typing performance is low, people might get frustrated. There are several text input methods in mobile phones. The study is conducted based on three text input methods such as T9 method. Multi-press with next button and Multipress with timeout method. However, there are problems caused by these three methods towards mobile phone application. There are numerous errors when typing messages using text input methods. Moreover, some text input methods are just too expensive and these methods take so much space in mobile phones' memory. Therefore, a lot of investigations or research must be done to determine which text input method that is able to gain more interest among stakeholders. Moreover, the new prototype recommended will be able to overcome the problems caused by existing text input methods. The purpose of the study for this research is to experiment the typical text input methods which are commonly used in mobile phones and also to determine the problems of typing messages which occur in many mobile applications. From this research, it is hoped that the new prototype which has been proposed can overcome the problems of typing messages. The methodologies used in this research are distributing questiormaires to one hundred and fifty one (151) students of the Faculty of Information Technology and Quantative, UiTM Shah Alam, as mobile application users. Moreover, this research has conducted an experiment involving six (6) of students as the test subjects. Based on the methodologies, the comparative results of the three text input methods are validated systematically. But more researches should be conducted in order to gain better information and find solutions to improve the functions of text input methods. Last but not least, it is also hoped that the users will enjoy better mobile application that they use in their daily lives.